2021
DOI: 10.1186/s12888-021-03281-4
|View full text |Cite
|
Sign up to set email alerts
|

Quality assessment of a consultation-liaison psychiatry service

Abstract: Background Consultation-Liaison Psychiatry (CLP) provides services for patients with medical-psychiatric comorbidity at the general hospital. Referral satisfaction is considered as one of the most important outcome measures of CLP interventions. Our aim was to assess the levels of satisfaction with the CLP service amongst medical staff at a university hospital in Denmark. Methods Medical staff answered an online survey regarding their experience wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Psychiatric consultation-liaison service is associated with reduced patients' length of general hospital stay, lowered mortality rate, and improved psychiatric symptoms (Chen et al, 2016;Singh et al, 2016;Sivin et al, 2020;Stein et al, 2020). However, it was found that the utilization rate of this service in general hospitals, which depends on the referral from treating health care professionals, was low ranging from 0.72% to 5.8% (Chen et al, 2016;Kovacs et al, 2021). The level of mental health literacy among health care professionals in general hospitals can be one of the main factors leading to this service gap (Chen et al, 2016;Giandinoto & Edward, 2014;Grover et al, 2017).…”
Section: Review-article2023mentioning
confidence: 99%
See 1 more Smart Citation
“…Psychiatric consultation-liaison service is associated with reduced patients' length of general hospital stay, lowered mortality rate, and improved psychiatric symptoms (Chen et al, 2016;Singh et al, 2016;Sivin et al, 2020;Stein et al, 2020). However, it was found that the utilization rate of this service in general hospitals, which depends on the referral from treating health care professionals, was low ranging from 0.72% to 5.8% (Chen et al, 2016;Kovacs et al, 2021). The level of mental health literacy among health care professionals in general hospitals can be one of the main factors leading to this service gap (Chen et al, 2016;Giandinoto & Edward, 2014;Grover et al, 2017).…”
Section: Review-article2023mentioning
confidence: 99%
“…Even though physical–mental comorbidity imposes a significant burden on individuals and societies, patients with physical–mental comorbidity were not adequately referred to the mental health service they needed (Chen et al, 2016; Kovacs et al, 2021; Sartorius et al, 2015). Psychiatric consultation–liaison service is an evidence-based service that provides biopsychosocial assessments for patients with physical–mental comorbidity and professional reciprocal interaction with general hospital health care professionals through education and patient management recommendations (Bourgeois & Sharpe, 2020; Grover et al, 2017; Mak & Wong, 2019; National Health Science England, 2016).…”
Section: Introductionmentioning
confidence: 99%